Kinerja Implementasi Kebijakan Pendataan Lengkap Koperasi, Usaha Mikro, Kecil dan Menengah Tahun 2022 di Sumatera Selatan - Hanafi, Hanafi; Saptawan, Ardiyan; Nengyanti, Nengyanti (Jurnal Pemerintahan dan Politik, 2023)
The data collection level in the Comprehensive MSME Census Activity 2022 in some regions of South Sumatra exceeded the target, while others fell short, despite facing similar challenges and receiving the same policy instruments. This study aims to analyze the implementation performance of the Comprehensive MSME Census Activity in South Sumatra and identify factors influencing performance gaps. Employing a descriptive analysis method with a qualitative approach, the study utilizes Van Meter & Van Horn's Implementation Process Model, considering six policy implementation aspects: policy standard and objective; the policy resources; inter-organizational communication and enforcement activities; the characteristics of the implementing agency; economic, social, and political conditions; and the disposition of the implementors. The research findings reveal a generally successful and comprehensive implementation performance of the 2022 Comprehensive MSME Census Activity in South Sumatra. Notably, the highest data collection achievement in Muara Enim District (171%) resulted from implementers' dispositions, modifying data collection mechanisms through discretionary initiatives. In contrast, the lowest achievement in Ogan Komering Ilir District (60%) was attributed to adhering strictly to procedural steps provided by policy framers. Effective policy implementation necessitates technological infrastructure readiness and the competence of involved personnel. Policy success hinges on government urgency to establish a Unified MSME Data System and specific task allocation based on professional needs. Impeding factors include field workers' inefficiency and persistent sectoral egoism affecting collaboration.